THE EFFECT OF GIVING INCENTIVES ON EMPLOYEE PERFORMANCE AT ANDI JEMMA AIRPORT OFFICE IN MASAMBA - Andi Kurniawan; Ria Mardiana Y; Wardhani Hakim (CV. Radja Publika, 2023)
This study looks at how well employees are doing their jobs and tries to understand why some employees are better than others in the andi jemma airport office in masamba. This is about how to make sure employees do their best work and feel excited to finish their tasks when they are given rewards or extra things that they like. This study shows how rewards can affect how well employees do their jobs. I used descriptive analysis to look closely at the information and understand it better, also a simple linear regression analysis and hypothesis testing. When we looked at how a certain thing (X) affects how well someone does their job (Y), we found that it had an effect on their performance. as for the results of the study showed the value of r square of 0.477.Tthese results indicate that the (X) variable affects the (Y) variable by 47.7%, while the remaining 53.3% is influenced by several other variables, such as comfort at work, fair leaders, reasonable instructions and others. I found that giving rewards to workers at the Andi Jemma Airport office in Masamba helped them do a better job.